Perfil de rendimiento de regatistas de élite de clase ILCA. Diferencias entre hombres y mujeres - Manzanares, A.; Encarnación-Martínez, A.; Chicoy-García, I.; Segado, F. (Archivos de medicina del deporte, 2023)
In sport sailing, there are three fundamental pillars of performance for dinghy sailors (physical condition, cognitive ability and equipment). One of the decisive moments in a single-handed dinghy race is sailing upwind, as it requires a high physical demand from the sailors to keep the boat flat and make the best decisions according to the tactical conditions of the race. The objective of the research is (i) to analyze the performance of elite sailors on the hiking position in a dynamic virtual sailing situation and (ii) to measure the lower body muscle fatigue in the hiking action. The sample consisted of 10 sailors from the Ilca sailing class and belonging to the Olympic teams of the Norwegian, Mexican and Spanish national teams, 6 of them men (Mage=31.67, SDage=6.861) and 4 women, (Mage=30.50, SDage=4.655). The fatigue protocol consisted of a static test and a dynamic test of the sac body position. Both tests measure the sailors` effort up to extreme fatigue or loss of position. The test was performed on the vSail-Trainer® sailing simulator, which allows to reproduce real sailing conditions and displays data on boat control variables. The results obtained show statistically significant differences between the group of women and men on boat speed (P=0.039), distance sailed (P<0.001) and hiking effort (P=0.002). There are statistically significant differences in lower body power pre and post fatigue test. This does not lead to the conclusion that the simulator is a valid tool to assess fatigue specifically in Ilca class sailors.